Design emocional e redesign: alternativa para o mercado infantil - Oliveira, Camila Dias de (2015)
This paper addresses the issue of redesign and emotional design as an alternative to child conscious market, focusing on the use of pieces of used clothes from their mothers in creating new pieces for the child. The study was intended audience the female child aged between 5-8 years of age, considering that it is at this stage that the child begins to develop the notion of value for things and believing that this practice learn early on conscious consumption. It attempted through a literature expose the emotional design concepts to understand the user relationship of affection with clothing, redesign concepts of adaptation and modifications clothing and upcycling to assist in the matter of the play use, and all this is reflected as a contributing means for reducing impacts on the environment caused by the fad system. In addition to the literature was used to apply a questionnaire to the public for collecting qualitative and quantitative data that served as support at the stage of development of the conscious collection for the public of this study.